2016
DOI: 10.1155/2016/7539780
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of the Pleural Fluid C-Reactive Protein in Parapneumonic Effusions

Abstract: Purpose. The aim of this study was to evaluate the sensitivity of pleural C-reactive protein (CRP) biomarker levels in identifying parapneumonic effusions. Methods. A single-center, retrospective review of 244 patients diagnosed with pleural effusions was initiated among patients at the Rabin Medical Center, Petah Tikva, Israel, between January 2011 and December 2013. The patients were categorized into 4 groups according to their type of pleural effusion as follows: heart failure, malignant, post-lung transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Furthermore, it confirms and extends the findings of previous investigations, in which pleural CRP levels were found to be higher in parapneumonic effusions than in other types of exudates. Izhakian et al [ 15 ] reported that pleural CRP levels were higher in parapneumonic effusion than in other effusion types, with a cut-off value of > 1.38 mg/dL. Pleural CRP had a low positive predicted value (37.6%) but a very high negative predicted value (96.7%), which suggests that it could be a powerful tool for excluding parapneumonic effusion as a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it confirms and extends the findings of previous investigations, in which pleural CRP levels were found to be higher in parapneumonic effusions than in other types of exudates. Izhakian et al [ 15 ] reported that pleural CRP levels were higher in parapneumonic effusion than in other effusion types, with a cut-off value of > 1.38 mg/dL. Pleural CRP had a low positive predicted value (37.6%) but a very high negative predicted value (96.7%), which suggests that it could be a powerful tool for excluding parapneumonic effusion as a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The studies were performed in nine countries and published from 2006 to 2017. Nine studies investigated the diagnostic performance of pleural CRP for PPE (15,16,(18)(19)(20)(21)24,27,28), and five studies used serum CRP to diagnose PPE (19,23,25,30,31). Seven assessed the potential of pleural CRP for differentiating CPPE from UPPE (14,16,17,21,22,26,29), two of which also determined the diagnostic role of serum CRP for CPPE (22,26).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…C-reactive protein (CRP) known as “acute-phase protein,” is synthesized by the liver in response to various stimuli and produced early in the inflammatory process. CRP is increased in the serum/plasma of patients with pneumonia and many studies also confirmed that increased pleural CRP (p-CRP) may present a possible biomarker for pleural infection, although with inconclusive results [ 4 , 5 , 6 ]. Additionally, high CRP levels (cut-off: 10 mg/dL) have been used as differentiator between complicated and non-complicated parapneumonic pleural effusions, with comparable AUC scores to those of widely accepted pleural pH and glucose [ 7 ].…”
Section: Introductionmentioning
confidence: 99%